Energy and exergy analysis of solid oxide electrolyser cell (SOEC) working as a CO2 mitigation device - Stempien, Jan Pawel (2013)
A simple thermodynamic model of SOEC system was presented in this paper. We performed energy and exergy analysis on the SOEC system to determine its optimal operating conditions. Parametric studies have been carried out to determine the effects of key operating parameters on the SOEC system. For given operating conditions and set assumptions, it was found that the optimal voltage applied to the SOEC system is 1.37 V. At this optimal value, the SOEC system is capable of achieving 50% and 60%, respectively, in terms of energy and exergy efficiency. It also achieved 67% reduction in CO2 with maximum feedstock conversion of 63.5%. The corresponding energy and exergy required to convert one kg of CO2 is 16.4 kJ and 7.2 kJ, respectively.